2007
DOI: 10.1007/s00125-007-0732-y
|View full text |Cite
|
Sign up to set email alerts
|

Glucose tolerance is negatively associated with circulating progenitor cell levels

Abstract: Aims/hypothesis Circulating progenitor cells participate in cardiovascular homeostasis. Depletion of the pool of endothelial progenitor cells (EPCs) is associated with increased cardiovascular risk. Furthermore, EPCs are reduced in the presence of classical risk factors for atherosclerotic disease, including diabetes mellitus. This study was designed to evaluate progenitor cell levels in volunteers with different degrees of glucose tolerance. Methods Cardiovascular parameters and the levels of circulating CD34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
69
3
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 49 publications
(59 reference statements)
9
69
3
4
Order By: Relevance
“…Endothelial progenitor cells in obesity K Tobler et al the best of our knowledge, the relation of circulating EPCs to ApoB, lipoprotein (a) and plasma free fatty acids has not been previously studied in detail. However, in accordance with our data, cholesterol [14][15][16] and triglycerides 14,16 were already described to be ineffective on CD34 þ /KDR þ and CD45 À /CD34 þ /VEGFR-2 þ /CD133 þ EPCs, whereas heterogeneous results were found on the effects of LDL on EPC numbers. 14,16,17 Although there are several reports on reduced EPCs in diabetes, 15,16 little attention has been paid to a direct association between EPCs and glycosylated hemoglobin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Endothelial progenitor cells in obesity K Tobler et al the best of our knowledge, the relation of circulating EPCs to ApoB, lipoprotein (a) and plasma free fatty acids has not been previously studied in detail. However, in accordance with our data, cholesterol [14][15][16] and triglycerides 14,16 were already described to be ineffective on CD34 þ /KDR þ and CD45 À /CD34 þ /VEGFR-2 þ /CD133 þ EPCs, whereas heterogeneous results were found on the effects of LDL on EPC numbers. 14,16,17 Although there are several reports on reduced EPCs in diabetes, 15,16 little attention has been paid to a direct association between EPCs and glycosylated hemoglobin.…”
Section: Discussionsupporting
confidence: 92%
“…So far, the investigation of EPC number in relation to hsCRP or hypertension led to heterogeneous results. [14][15][16][18][19][20] However, for determination of extremely rare eventsFas is the case in EPC analysisFa very high number of PBMCs must be analyzed to obtain reliable results. As an aside, we had the possibility to evaluate about 30-50 times more events in this study compared with most of the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…People with impaired glucose tolerance have been reported to have decreased CD34+ progenitor cell subtypes, but not reduced CD34+ VEGFR-2+ (EPC) cells, and post-glucose challenge glucose levels independently related to both CD34+ and CD34+ VEGFR-2+ levels [42], but in this group metabolic abnormalities would be more extensive and not restricted to hyperglycaemia.…”
Section: Discussionmentioning
confidence: 92%
“…However, putting these issues aside, the glucose status of all participants was characterised by fasting analysis and glucose tolerance test, and correlated with peripheral blood samples analysed for CD34 + / VEGFR2 + cell counts. The study showed that CD34 + and CD34 + /VEGFR2 + counts were negatively correlated with both fasting and post-challenge blood glucose [21]. In a previous study by the authors, diminution of the number of cells carrying the same surface markers correlated with peripheral vascular disease in diabetic individuals [24].…”
mentioning
confidence: 67%
“…In this issue of Diabetologia, Fadini and colleagues make an association between circulating EPC numbers and glucose tolerance in non-diabetic individuals [21], extending previous data from the same authors on circulating EPC numbers in diabetes as a barometer of cardiovascular risk [22,23]. Recognising that glucose tolerance is a continuum between values in the normal range and in diabetes, the results are not necessarily surprising, yet they are important as we seek to identify and intervene earlier to help patients at risk of cardiovascular disease.…”
mentioning
confidence: 99%